Indústria cultural, semiformação e esclarecimento: uma discussão a partir do pensamento de Adorno para uma educação emancipatória - Santos, Darlla Dalila Pontes dos (2022)
The debate on the life of men in society reveals issues of the social context, such as religion, family, politics, education, among others. In these items, the main agent is the human being, as he is the one who dictates the existence and format of these instances. Therefore, it is necessary to reflect on how their training takes place and what can be done so that it is directed towards ethical values. Learning takes place through coexistence in different social spheres, including the use of the media, through which it is possible to obtain a lot of information. All this refers to the question of cultural formation, which can contribute to the elevation of man or to his debasement. For the philosopher Theodor Adorno, cultural formation in capitalism has become semi-culture, because the production of cultural goods on a large scale has directed them towards commodification, transforming itself into an industry whose main purpose is profit. In this sense, the role of valuing human subjectivity, previously directed to culture, has not been evidenced, and consumers of the cultural industry, including children and young people, are conditioned to standardized goods and increasingly influenced by this standardization, leading them to a semi-formation and an estrangement of their individuality. However, Adorno believes that education, especially in the school environment, can be an instrument for alleviating and/or overcoming this semi-formation, and can lead the student to enlightenment and emancipation. In this same context, the debate on the training of education professionals has also grown, especially pedagogue teachers – since they work directly in the training of children and young people –, with a view to a more reflective, enlightened and autonomous educational performance. Based on these considerations, the objective of this research was to investigate whether, in the Pedagogy Course, theoretical foundations are provided to allow future pedagogues to understand issues arising from capitalism and that influence, in a negative way, the formation of their future students (children and young people), with emphasis on the issues of the cultural industry and semi-education, pointing out the need for clarification and autonomy as a mediation for the formation of the subject, with a view to an emancipatory education. Thus, this work fits as a qualitative research, with a theoretical framework based on Adorno’s thinking, in addition to the application and analysis of questionnaires with undergraduates and graduates of the Pedagogy Course. As a result of the research, it can be seen that, although the Pedagogy Course has, from several disciplines, theoretical elements that justify a possible critical thinking, there is still a lack of understanding of many theories, which, in turn, can influence the education of children and young people. However, the research also identified that the theory of the philosopher Theodor Adorno about the existing culture can help such understanding, especially in relation to the criticism he makes to the question of the cultural industry and semi-formation, pointing out the need for an emancipatory education for clarification, autonomy and subject formation (children and youth). Therefore, it points to the need for the Adornian theory to be disseminated and known by educators in general.